Assessment of clinical skills in cardiovascular physiotherapy: Objective Structured Clinical Examination (OSCE) - Ferreira, Isabelle Tiburcio Pecin (2024)
Introduction: It is crucial to integrate realistic assessment approaches for cardiovascular physiotherapeutic skills in the professional context. The Objective Structured Clinical Examination (OSCE) is notoriously reliable and valid. However, understanding the student's perception after this experience is important for readjusting this assessment. Objective: To evaluate the strengths and limitations of applying the OSCE to undergraduate students during the Supervised Cardiovascular Physiotherapy Internship. Methods: Descriptive, qualitative, observational and cross-sectional study. The students were submitted to the OSCE and upon completion, a questionnaire was administered to assess perception, which contains seven items: A) general organization of the exam; B) clinical cases and instructions for the examination; C) adequacy of the tasks required; D) quality of post-exam explanations; E) complexity of the content involved, in which the student could assign a grade from 1 to 5 (1 – insufficient; 2 – regular; 3 – good; 4 – excellent; 5 – excellent); F) difficulty with time management; and G) emotional stress. The items F and G were rated: 1 - very low; 2 – low; 3 – medium; 4 – high; and 5 - very high. Results: Fifty-one students responded to the questionnaire. For items A, B, C, D and E, the most prevalent response was excellent (72.5%, 43.1%, 52.9%, 88.2% and 54.9% respectively). Regarding item F, 54.9% of students reported medium difficulty managing time. Regarding item G, 94.2% reported a very high level of emotional stress. Conclusion: The application of the OSCE provided experiences of clinical cases with adequate complexity in an organized manner and with an enriching final evaluation.